The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1007/bf02707456
|View full text |Cite
|
Sign up to set email alerts
|

Optical absorption and fluorescent behaviour of titanium ions in silicate glasses

Abstract: Titanium in normal melting conditions in air atmosphere present as Ti 4+ ion in basic silicate glasses exhibited an ultraviolet cutoff in silicate glasses, viz. soda-magnesia-silica, soda-magnesia-limesilica and soda-lime-silica glasses. This indicates that Ti 4+ ion can be a good replacement for Ce 4+ ion in producing UV-absorbing silicate glasses for commercial applications. The wavelength maxima at which the infinite absorption takes place in glasses was found to be around 310 nm against Ti-free blank glass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…It has also been verified that although natural hectorite presents a similar blue emission often attributed to [SiO 2 ] 2− centers, it has different luminescence features than have been observed for halogen-hectorites [24]. Also, previous reports have shown that Ti species can occur as impurities in silicates, generating similar emission features as reported for silicate glasses [54], fluorohectorites [23] and chlorohectorites [24]. The materials studied in the current work have low contents of Ti, confirmed from their respective XRF spectra (Figure 2).…”
Section: Appl Sci 2017 7 1243supporting
confidence: 53%
“…It has also been verified that although natural hectorite presents a similar blue emission often attributed to [SiO 2 ] 2− centers, it has different luminescence features than have been observed for halogen-hectorites [24]. Also, previous reports have shown that Ti species can occur as impurities in silicates, generating similar emission features as reported for silicate glasses [54], fluorohectorites [23] and chlorohectorites [24]. The materials studied in the current work have low contents of Ti, confirmed from their respective XRF spectra (Figure 2).…”
Section: Appl Sci 2017 7 1243supporting
confidence: 53%
“…It can be concluded that the effective PL of Ce ions in glasses was regulated by the CeO 2 /TiO 2 ratio in them. It was concluded that Ti was present mainly in the tetravalent state according to the results for samples of Ce-Ti-containing glasses (2)(3)(4)(5)(6)(7)(8) and the literature [30][31][32]. Luminescence in the range 500-560 nm that is noticeably different from that at longer wavelength for Ti 3+ ions is characteristic of Ti 4+ ions.…”
mentioning
confidence: 87%
“…Samples from the 2nd Series deviate a little from series 1-3, indicating that CaO might affect the Urbach energy, as well. Kumar et al [48] also found that the absorption edge obeys the Urbach rule at low TiO 2 additions (0.1 wt%), however, no Urbach energy data were given. The Urbach energy has not frequently been determined, however, Abdel-Baki et al [13], determined the Urbach energy values for some glasses in the TiO 2 -Na 2 O-SiO 2 ternary.…”
Section: Optical Absorption and Absorption Edgementioning
confidence: 98%